Pengaruh Gaya Hidup, Kepercayaan Konsumen, Dan Nilai Yang Dirasakan Terhadap Minat Beli Thrift Shop di Sidoarjo - Sari, Dewi Komala; Maulidyah, Nur Laila; Nugroho, Tofan Tri (Airlangga Journal of Innovation Management, 2024)
The purpose of this study was to determine the effect of lifestyle, consumer trust, and perceived value on consumer buying interest in Thrift Shop products in Sidoarjo. This research uses a quantitative approach with the population being Generation Z and who have purchased Thrift Shop products in Sidoarjo. The sampling technique of this research was carried out by non-probability sampling method with purposive sampling technique with a total of 102 respondents. The data source collection technique used in this study is primary data using an online questionnaire through Google form media and disseminated through social media. Based on the results of this study, it proves that Lifestyle affects purchase intention, consumer trust affects purchase intention and perceived value affects Thrift Shop purchase intention in Sidoarjo. Customers consider the perceived value of Thrift Shop to be good, thus having an impact on buying interest. Perceived value makes sense to consumers, encouraging high buying interest in thrift shop products The managerial implications of the discussion and analysis results in research on lifestyle consumer trust and perceived value in thrift shop products in the functional and symbolic dimensions are expected to be useful for interested parties, especially for second-hand clothes sellers. This study implies that consumers have a perceived value related to the quality and benefits of the products they will get. So, this has implications for consumers in making decisions to buy thrift shop products